The Dynamic Model of Water Balance in A Sub-Basin - Dea Evantri; Muh. Yanuar J. Purwanto; Nora Pandjaitan; Roh Santoso Budi Waspodo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Management of water resources in a river basin requires a new approach. The availability of water is a basic thing that must be considered given the increasing need for water. This study aimed to develop a water balance model in the Upper Bekasi River Sub Basin. In this study water balance model of the Bekasi River Sub Basin was built with several variables that affect water demand and availability, namely population growth rate, public facilities, and efforts to utilize resources. In this research, water supply and demand modelling was carried out using a dynamic system supported by Vensim software. Simulations were carried out from 2012 to 2045. The increase in population growth was directly proportional to the increased in population water needs. This dynamic model simulation used the application of rainwater harvesting and water-saving behaviour. Water demand for the Bekasi River Sub Basin was equal to 156.649.000 m3/year. The availability of surface water was 138.127.680 m3/year and had not been able to meet the water needs. The dynamic model showed that the water balance will be deficit in 2031, namely 51.883.200 m3/year. However, with the application of the water saving scenario, the water balance has a surplus of 258.564.000 m3 / year until the end of the simulation. Water reducing behavior can be used as an efficient method of water utilization. Keywords: Population, Rainwater harvesting, Simulation, Water management, Water resource